Sexual Harassment in the Workplace : Perspectives, Frontiers, and Response Strategies. - Stockdale, Margaret S. (Women and Work: A Research and Policy Series., 1996)
Sexual harassment is now a universally recognized topic of concern for employers as well as employed women. The contributors to this volume provide a comprehensive look at what we know about sexual harassment. Their findings are grounded in theory, research and practice.